SOSIALISASI STRATEGI PEMASARAN DIGITAL KEPADA UMKM DI DESA BOGOR BARU KEPAHIANG - Zella, Zella; Saputra, Eki (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
There is a lack of understanding about digital marketing techniques, therefore it is necessary to disseminate information about digital marketing strategies and how to implement them. The aim of this activity is to provide training on the importance of digital marketing in today's technological era and to be able to implement it effectively and efficiently. The method used is through socialization using power point (PPT) media. The results of the activity showed that the community responded positively, because the benefits of this activity had an impact on increasing sales and visibility of their products. For the sustainability of MSME businesses, it is recommended that further training, mentoring, improvement of facilities and infrastructure, collaboration with other parties, and regular evaluation of marketing strategies be carried out.